2016
DOI: 10.1111/josi.12193
|View full text |Cite
|
Sign up to set email alerts
|

Children's Reasoning about Poverty, Economic Mobility, and Helping Behavior: Results of a Curriculum Intervention in the Early School Years

Abstract: This study evaluated the efficacy of an inquiry-based poverty curriculum unit on students' beliefs about causes of poverty, economic mobility, and helping behaviors. Participants were 89 kindergarten, first-and second-grade students (mean age = 6.81 years, SD = .93) across two intervention and two control classrooms. Students in intervention classrooms participated in a 5-to 7-week curriculum unit focused on poverty. Preintervention results showed no differences in outcomes by condition. Postintervention resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(53 citation statements)
references
References 43 publications
0
53
0
Order By: Relevance
“…In six studies, participants in the control group were waiting to be assigned to an intervention condition (waiting list, WL), and in seven studies the control group engaged in a different type of activity that did not explicitly promote prosocial behavior (placebo, PL). Examples of the placebo condition include a science inquiry unit investigating ecosystems (Mistry et al., 2016) and exercises intended to improve reading and study skills (Fung, 2008). In one study, only measurement was performed in the control group, but no intervention (Böckler, Tusche, Schmidt, & Singer, 2018).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In six studies, participants in the control group were waiting to be assigned to an intervention condition (waiting list, WL), and in seven studies the control group engaged in a different type of activity that did not explicitly promote prosocial behavior (placebo, PL). Examples of the placebo condition include a science inquiry unit investigating ecosystems (Mistry et al., 2016) and exercises intended to improve reading and study skills (Fung, 2008). In one study, only measurement was performed in the control group, but no intervention (Böckler, Tusche, Schmidt, & Singer, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Of the 11 studies with multiple intervention groups (MI), eight compared different types of prosocial interventions. Three studies used the same intervention in two groups but with slightly different procedures, appropriate for the participants’ age range or developmental stage (Kramer, Caldarella, Young, Fischer, & Warren, 2014; Mistry et al., 2016) or adapted for specific cultures (Luengo Kanacri et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…In fact, Leahy () found that asking others for money was 6‐year‐olds’ most commonly mentioned method for both how a poor person could become rich and how they themselves could become rich in the future. Whereas older children often mention trait‐like distinctions when defining the rich and the poor, preschool‐age children rarely do so (Leahy, ; see also Mistry et al., ): They favor possessions over dispositions when describing such groups, suggesting that material possessions are more salient than stereotype‐driven traits in young children's mental representations of socioeconomic groups. Moreover, preferences for resource‐rich people are evoked even through contrasts as subtle as who owns 5 versus 4 jars of play‐dough (Li et al., ).…”
Section: Children's Social Preferences For the Resource Richmentioning
confidence: 99%
“…One perspective often left out of public discussion is that of young people. Mistry, Nenadal, Griffin, Zimmerman, Cochran, Thomas, and Wilson () examine poverty and inequality from the perspective of middle and upper class children. Their research is premised on the idea that class bias begins at a young age, and that we need to take steps to understand how children see this important issue if we want to shift the American public's attitudes about the poor.…”
Section: Structural Framework and Research Topicsmentioning
confidence: 99%